Promotion of Quality Seed for Potato - International Potato Center (International Food Policy Research Institute, 2014)
This data study contains data from on-farm trials to compare the performance of quality seed versus poor quality seed and field day at flowering and harvesting season. Project title: Promotion of Quality Seed for Potato. Project abstract: Quality seed is more expensive than ordinary seed. While farmers in most communities demand access to quality seed, few farmers are actually willing to pay the premium associated with seed of better quality. It is therefore necessary to promote the merits of quality seed so as to create a farmer-based demand and market for quality seed. Project website: http://africa-rising.net